Vaginal prevalence of human papillomavirus infections in women with uterovaginal aplasia before and after laparoscopically assisted creation of a neovagina: a prospective epidemiological observational study. (20th August 2018) - Rall, KK; Schoenfisch, B; Schoeller, D; Stefanescu, D; Koelle, A; Henes, M; Huebner, M; Taran, FA; Seeger, H; Iftner, A; Iftner, T; Brucker, SY
Abstract : Objective: To study vaginal as opposed to cervical human papillomavirus (HPV) acquisition with regard to true prevalence, HPV types, and the role of co‐factors in virgins and after their sexual debut. Design: Prospective epidemiological observational study. Setting: University hospital specialised in genital malformations. Population: Women diagnosed with Mayer–Rokitansky–Küster–Hauser syndrome (MRKHS) and undergoing neovaginoplasty between November 2011 and July 2017. Methods: This is a prospective study including 186 women with MRKHS before and after sexual debut. Main outcome measures: Conventional vaginal cytology and different HPV tests were performed at surgery and during routine gynaecological follow‐up 1, 3, 6 and ≥ 11 months after surgery and risk factors were documented. Results: The mean age of all women at surgery was 20.1 years (SD 5.4), mean body mass index (BMI) was 22.1 kg/m 2 (SD 4.6). In 83 vaginal samples from 41 different women at least one of the HPV tests was positive. Thirty‐three different HPV types were detected. The prevalence of 41/186 = 22.0% as well as type distribution are comparable with those found in a young German female population. The overall rate of acquisition was clearly associated with sexual activity and smoking habits. Out of 367 Papanicolaou smears only six were abnormal with Pap IIID (MN II) and no obvious vaginal lesion was detected. Conclusions: Vaginal HPV prevalence and HPV types in previously virgin women after creation of a neovagina are not different from the acquisition of cervical infections in the general population and is clearly associated with sexual activity and with smoking habits. However, abnormal Papanicolaou smears are rarely seen. Tweetable abstract: Vaginal HPV prevalence after creation of a neovagina is similar to that on the cervix in the general population. Tweetable abstract: Vaginal HPV prevalence after creation of a neovagina is similar to that on the cervix in the general population.